Korean Economic Miracle in the Mirror of the Samsung Chaebol - Kamen Nam (Bulgarian Journal of International Economics and Politics, 2025)
The study aims to examine the phenomenon of the “Korean economic miracle” through the prism of the genesis and development of one of the leading Korean corporations – Samsung, whose origins are discussed against the background and in connection with the historical challenges facing the Korean nation and analysed in the context of East Asian regional specificity in socio-economic development. Introducing the concept of chaebol, the study reveals key aspects of the genesis of the structural-functional nature of Korean society and their impact on the contemporary state of the Republic of Korea using the example of the creation and development of the Korean corporation Samsung. The analysis reveals the pillars of Samsung’s success – tradition, ancestral memory, statehood, and education, within the historical context of their development. The study builds on a significant amount of historical, ethnographic and ethno-cultural facts, as well as economic information. In the course of the analysis, a number of causal relationships have been deduced that are directly related to the formation of the contemporary highly developed Korean state and society.